Improvement of Electric Field Stress Control on Polymeric Outdoor Insulator - Haslan, Muhammad Shazwan; Abd Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2025)
The electric field stress control of polymeric outdoor insulators is crucial for ensuring their reliability and longevity in service. This study delves into the impact of insulator design managing electric field stress on outdoor polymeric insulators. Excessive electric stress, in conjunction with contaminants and moisture, can lead to surface arcing, potentially resulting in insulator flashover. By employing the Finite Element Method (FEM), the electric field and potential distributions along the insulator’s surface leakage path were computed. The material selection and characterized boundary within the FEM framework. Comparative analyses of field and equipotential profiles for insulators with properties of weather shed and corona ring design under dry and uniformly contaminated surface conditions were conducted. The findings underscore the significance of utilizing innovative materials and computational methods to enhance stress control mechanisms for polymeric outdoor insulators, thereby mitigating the risks associated with electrical breakdown and flashover events.